ASSESSING INVENTIVE THINKING USING RASCH MODEL - Eka Ad'hiya; Maefa Eka Haryani; Rodi Edi; Diah Kartika Sari; Nadila Nur Savitri (SPEKTRA: Jurnal Kajian Pendidikan Sains, 2025)
This study aims to analyze the inventive thinking of students in the chemistry education study program at Sriwijaya University using Rasch modeling. This study is a quantitative study with a cross-sectional study design. This study was conducted at the Chemistry Education Study Program, FKIP Sriwijaya University. The subjects of this study consisted of 159 students from 3 active student classes of the chemistry education study program in 2024. The results of the study were analyzed using the RASCH Model with the help of the WINSTEP application, namely 1) Validity analysis (Person and item fit) shows that the Person/item fit Mean Square (MNSQ) for the inventive thinking instrument is in the range of 0.5-1.5 so that it is included in the category of "productive to use," while the reliability analysis (Person and item reliability) shows the results that r> 0.91 so that it is reliable; 2) Inventive thinking analysis (Person measure analysis) shows the results that there are 135 participants who fit/meet the Rasch modeling criteria; 3) Analysis of data bias between student generations (DIF analysis) shows that DIF only occurs in item KV3, where the probability is <0.05. This indicates that item KV3 is detrimental or beneficial to a particular generation; 4) Analysis of the science-related attitude and inventive thinking categories (Logit value of person) shows that 4.06% are in the high category, 94.3% are in the medium category, and 1.64% are in the low category; 5) Analysis of differences in inventive thinking between generations (Independent t-test) shows that the calculated t is smaller than the t table value, so there is no significant difference. The results of this study can conclude that there is no significant difference in inventive thinking ability between student levels, and most students are in the medium category.